2005
DOI: 10.5751/es-01353-100214
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Services and Human Well-Being: a Participatory Study in a Mountain Community in Portugal

Abstract: Ecosystem services are essential for human well-being, but the links between ecosystem services and human well-being are complex, diverse, context-dependent, and complicated by the need to consider different spatial and temporal scales to assess them properly. We present the results of a study in the rural community of Sistelo in northern Portugal that formed part of the Portugal Millennium Ecosystem Assessment. The main purpose of our study was to assess the linkages between human well-being and ecosystem ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
115
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(128 citation statements)
references
References 21 publications
6
115
0
7
Order By: Relevance
“…Rural populations still value the quality of their environment and its scenic beauty (Bell et al 2009;Pereira et al 2005), but the working conditions in many of these regions have always been difficult. Terraces are some of the most admired cultural landscapes in Mediterranean areas, but locals often use the expression "slavery land" to describe the harshness of the working conditions (Pereira et al 2005).…”
Section: Did Traditional Rural Populations Live Well?mentioning
confidence: 99%
See 2 more Smart Citations
“…Rural populations still value the quality of their environment and its scenic beauty (Bell et al 2009;Pereira et al 2005), but the working conditions in many of these regions have always been difficult. Terraces are some of the most admired cultural landscapes in Mediterranean areas, but locals often use the expression "slavery land" to describe the harshness of the working conditions (Pereira et al 2005).…”
Section: Did Traditional Rural Populations Live Well?mentioning
confidence: 99%
“…Terraces are some of the most admired cultural landscapes in Mediterranean areas, but locals often use the expression "slavery land" to describe the harshness of the working conditions (Pereira et al 2005).…”
Section: Did Traditional Rural Populations Live Well?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, only few studies of ecosystem services have addressed stakeholders' perspective in the valuation of ecosystem services (Pereira et al 2005;Lamarque et al 2011).…”
mentioning
confidence: 99%
“…However, considering spatial and temporal scales, the links between ecosystem services and human activities are more complicated (Pereira et al, 2005). According to the report of Millennium Ecosystem Assessment (MEA), it showed that human activities had induced more rapid and extensive changes in ecosystems over the past 50 years compared to other period, which mainly due to the rapidly growing demands of humans for food, fresh water, timer, fiber and fuel etc.…”
Section: Introductionmentioning
confidence: 99%